Character Building of “Sanaman Mantikei” Folklore from Central Kalimantan - Afdalia, Tiara; Perdana, Indra; Luardini, Maria Arina (Journal Of Foreign Language Learning and Teaching, 2022)
The folklore entitled Sanaman Mantikei is one of the legends originating from Central Kalimantan. Folklore as literacy material can be used in the teaching and learning process to strengthen student character building. This study aims to describe the values of character building in the folklore legend "Sanaman Mantikei". The method used in this study was a qualitative descriptive method with the research data source in the form of Central Kalimantan Folklore books. The results of the study showed that the folklore "Sanaman Mantikei" contains character building values (1) hard work; (2) creativity; and (3) love-peace. The values of character building contained in these folktales form the basis that folklore can be used as a medium to introduce cultural stories of an area and as a means of educating students' character in the teaching and learning process.